Impairment of Several Immune Functions and Redox State in Blood Cells of Alzheimer’s Disease Patients. Relevant Role of Neutrophils in Oxidative Stress - Vida, Carmen; Martinez de Toda, Irene; Garrido, Antonio; Carro, Eva; Molina, José Antonio; De la Fuente, Mónica (Frontiers in Immunology, 2018)
Since aging is considered the most risk factor for sporadic Alzheimer´s Disease (AD), the age-related impairment of the immune system (immunosenescence), based on a chronic oxidative-inflammatory stress situation, could play a key role in the development and progression of AD. Although AD is accompanied by systemic disturbance, reflecting the damage in the brain, the changes in immune response and redox-state in different types of blood cells in AD patients have been scarcely studied. The aim was to analyze the variations in several immune functions and oxidative-inflammatory stress and damage parameters in both isolated peripheral neutrophils and mononuclear blood cells, as well as in whole blood cells, from patients diagnosed with mild (mAD) and severe AD, and of age-matched controls (elderly healthy subjects) as well as of adult controls. The cognitive decline of all subjects was determined by Mini-Mental-State-Examination (MMSE) test (mAD stage was established at 20≤MMSE≤23 score; AD stage at <18 MMSE; elderly subjects >27 MMSE). The results showed an impairment of the immune functions of human peripheral blood neutrophils and mononuclear cells of mAD and AD patients in relation to healthy elderly subjects, who showed the typical immunosenescence in comparison with the adult individuals. However, several alterations were only observed in severe AD patients (lower chemotaxis, LPS-lymphoproliferation and IL-10 release; higher basal-proliferation, TNF-α release and IL-10/TNF-α ratio), others only in mAD subjects (higher adherence), meanwhile others appeared in both mAD and AD patients (lower PHA-lymphoproliferation and higher IL-6 release). This impairment of immune functions could be mediated by: 1) the higher oxidative stress and damage also observed in blood cells from mAD and AD patients, and in isolated neutrophils (lower GSH levels; high GSSG/GSH ratio and GSSG and MDA contents); and 2) the higher release of basal pro-inflammatory cytokines (IL-6, TNF-α) found in AD patients. Because the immune system parameters studied are markers of health and rate of aging, our results supported an accelerated immunosenescence in AD patients. We suggest the assessment of oxidative stress and function parameters in peripheral blood cells as well as in isolated neutrophils and mononuclear cells, respectively, as possible markers of AD progression.